2003
DOI: 10.1023/a:1020615830765
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: From Pseudomonas chlororaphis D-TR 133 a pyoverdine was isolated and its primary structure were elucidated by spectroscopic methods and degradation reactions. Despite some structural differences, its Fe(III) complex and that of the pyoverdine from Pseudomonas fluorescens CHA0 were taken up by either strain with a high rate. This is explained by a structural similarity between the two pyoverdines which were shown to differ in their structures only by the replacement of Lys by Ala in the C-terminal part of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Instead, P. fluorescens very likely utilizes the S. ambofaciens siderophores desferrioxamine B and coelichelin as xenosiderophores, thanks to its FoxA receptor. In contrast to most studies, in which the use of xenosiderophores was revealed indirectly through the addition of purified siderophore to the growth medium (44)(45)(46)(47), binding affinity assays (11,48), or native PAGE and surface plasmon resonance (49) or with labeled iron (11,50,51), we revealed potential iron piracy through a direct interaction between a Gram-positive and a Gram-negative bacterium. This potential piracy likely occurs only in one direction.…”
Section: Discussioncontrasting
confidence: 92%
“…Instead, P. fluorescens very likely utilizes the S. ambofaciens siderophores desferrioxamine B and coelichelin as xenosiderophores, thanks to its FoxA receptor. In contrast to most studies, in which the use of xenosiderophores was revealed indirectly through the addition of purified siderophore to the growth medium (44)(45)(46)(47), binding affinity assays (11,48), or native PAGE and surface plasmon resonance (49) or with labeled iron (11,50,51), we revealed potential iron piracy through a direct interaction between a Gram-positive and a Gram-negative bacterium. This potential piracy likely occurs only in one direction.…”
Section: Discussioncontrasting
confidence: 92%
“…To develop future analytical tools, with fast throughput as in plate-reader technology, it would be desirable to separate between the optical signaling of metal coordination and the surface-adhesive moiety. It occurred to us that, like in the siderophores of the pyoverdin family, the iron(III) binding site could be fused with a fluorescent probe into a single functionality (Figure ).
1 Fluorescent bidentate 2,3-diamino-6,7-dihydroxy-quinoline binding units (a) of pyoverdin PaA 40 and (b) of azotobactin δ
…”
Section: Introductionmentioning
confidence: 99%
“…One instance is the production of a pyoverdine siderophore with two structural variants, whose amino acid structure differs in the incorporation of alanine or glycine [30]. However, the substitution of glycine was restricted to a specific alanine residue in the siderophore and the glycine-containing siderophore was a minor portion of the total siderophore production and could not be independently isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The NRPS-dependent biosynthetic pathways of a number of siderophores have been well studied, including enterobactin [2426], pyochelin [27], yersiniabactin [28], vibriobactin [29], mycobactins [15], and pyoverdine [30, 31]. The amphiphilic peptidic marine siderophores are likely also assembled by NRPS multienzyme systems due to the inclusion of unique features such as D-amino acids, N-terminally attached fatty acid chains, and heterocyclic elements [23, 32].…”
Section: Introductionmentioning
confidence: 99%